Review on Computer-Aided Design and Manufacturing of Drug Delivery Scaffolds for Cell Guidance and Tissue Regeneration - Salerno, Aurelio; Netti, Paolo A. (Frontiers in Bioengineering and Biotechnology, 2021)
In the last decade, additive manufacturing (AM) processes have updated the fields of biomaterials science and drug delivery as they promise to realize bioengineered multifunctional devices and implantable tissue engineering (TE) scaffolds virtually designed by using computer-aided design (CAD) models. However, the current technological gap between virtual scaffold design and practical AM processes makes it still challenging to realize scaffolds capable to encode all structural and cell regulatory function of the native extracellular matrix (ECM) of health and diseased tissues. Indeed, engineering porous scaffolds capable to sequester and present even complex array of biochemical and biophysical signals in a time and space regulated manner, requires advanced automated platforms suitable to process simultaneously biomaterials, cells and biomolecules at nano-metric size scale. The aim of this work was to review the recent scientific literature about AM fabrication of drug delivery scaffolds for TE. This review focused on bioactive molecules loading into three-dimensional (3D) porous scaffolds and, their release effects on cell fate and tissue growth. We reviewed CAD-based strategies, such as bioprinting, to achieve passive and stimuli-responsive drug delivery scaffolds for TE and cancer precision medicine. Finally, we describe authors’ perspective regarding next generation of CAD techniques and, the advantages of AM, microfluidic and soft lithography integration for enhancing 3D porous scaffolds bioactivation towards functional bioengineered tissues and organs.